2021
DOI: 10.1136/gutjnl-2020-323426
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG induces cGAS/STING- dependent type I interferon and improves response to immune checkpoint blockade

Abstract: ObjectiveOur goals were to evaluate the antitumour efficacy of Lactobacillus rhamnosus GG (LGG) in combination with immune checkpoint blockade (ICB) immunotherapies on tumour growth and to investigate the underlying mechanisms.DesignWe used murine models of colorectal cancer and melanoma to evaluate whether oral administration of LGG improves the efficacy of ICB therapies. We performed the whole genome shotgun metagenome sequencing of intestinal contents and RNA sequencing of dendritic cells (DCs). In a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 50 publications
1
115
0
1
Order By: Relevance
“…The role of the STING pathway in potentiating the efficacy of immunotherapy, was also proven by Shi et al ( 136 ). In agreement with the findings of Si et al ( 135 ), Shi et al ( 136 ) observed that a specific gut microbe, Bifidobacterium spp., potentiated anti-CD47 immunotherapy via the stimulation of STING in DCs in tumor-bearing mice.…”
Section: Gut Microbiota and Immune Checkpoint Inhibitionsupporting
confidence: 91%
See 3 more Smart Citations
“…The role of the STING pathway in potentiating the efficacy of immunotherapy, was also proven by Shi et al ( 136 ). In agreement with the findings of Si et al ( 135 ), Shi et al ( 136 ) observed that a specific gut microbe, Bifidobacterium spp., potentiated anti-CD47 immunotherapy via the stimulation of STING in DCs in tumor-bearing mice.…”
Section: Gut Microbiota and Immune Checkpoint Inhibitionsupporting
confidence: 91%
“…More recently, in 2021, Si et al ( 135 ) evaluated the therapeutic efficacy of administering a single bacterial strain, Lactobacillus rhamnosus GG (LGG) in combination with ICI immunotherapy. Pivotally, the oral administration of LGG significantly improved the efficacy of ICIs and reduced tumor growth in CRC and melanoma mouse models.…”
Section: Gut Microbiota and Immune Checkpoint Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of mice after HCC development with 3′3′-cAIMP, a cyclic dinucleotide STING agonist, effectively reduces the tumor size in cGAS –/– mice, which cannot generate 2′3′-cGAMP ( Thomsen et al, 2020 ). In addition, Lactobacillus rhamnosus GG induces cGAS/STING-dependent IFN-β production and improves the response to anti-programmed cell death 1 (PD-1) immunotherapy ( Si et al, 2021 ). Therefore, regulation by STING pathway agonists may reverse the development of HCC and is expected to be an effective treatment strategy.…”
Section: Cgas-sting Pathway In Liver Diseasesmentioning
confidence: 99%